Forget Paris [videorecording (DVD)] - Crystal, Billy; Crystal, Billy; Winger, Debra, 1955-; Mantegna, Joe (Warner Home Video, 2017)
A couple who fell in love in Paris have trouble adjusting to the regular problems of married life.